A Review : Performance Analysis of Single Board Computer Technology as an IoT System - Erfan, Rohadi; Cahya, Rahmad; Septian, Enggar Sukmana; Aida, Sartimbul; Kismet, Hong Ping; Annie, Joseph; Dayang Azra, Awang Mat; Mohammad Faried, Rahmat (2025)
The development of Internet of Things (IoT) technology has driven the demand for cost-effective server solutions capable of managing large volumes of data, thereby creating efficiencies in data management to support smart digitalization. Single Board Computer (SBC) technology, such as Raspberry Pi and Tinkerboard have been developed over the years to offer another alternative for powering energy efficient server infrastructure that has decent performance for diverse dataset processing for the IoT. Advantages provided by such devices make SBC a potential candidate for IoT servers. Such low-cost, low power machines can offer required computing resources to facilitate various IoT applications, such as edge processing, data aggregation and analysis. This paper compares single board computer products as IoT servers, such as Raspberry Pi 3, Raspberry Pi 4 and Asus Tinkerboard, from the case study of room sensor monitoring in Internet of Things. It can be seen from the test results that the Raspberry Pi 4 is more suitable to deploy IoT application at a low price when the CPU response time is 62 seconds, and the CPU response time is 96 seconds for the Raspberry Pi 3 and 64 seconds for the Tinker Board. This work will give useful advice to IoT developers, readers to choose an appropriate Single Board Computer for their environmental sensing work.